The Influence of Digital Marketing and Neurolinguistic Programming on Increasing the Level of Welfare and Business Development in MSMEs in East Java - Kartika, Chandra; Sri Lestari, Veronika Nugraheni; Indrawati, Mei; Utari, Woro; Sarie, Rena Febrita (LPPM of NAROTAMA UNIVERSITY, 2025)
This study aims to examine the influence of digital marketing and Neuro Linguistic Programming (NLP) marketing on the improvement of welfare and business development of Micro, Small, and Medium Enterprises (MSMEs) in East Java, Indonesia. The research adopts a quantitative approach using a survey method. Data were collected from 200 MSME respondents across various sectors in East Java. Structural Equation Modelling using Partial Least Squares (SEM-PLS) was employed to analyse the relationships between variables. The findings indicate that digital marketing has a significant and positive effect on both the welfare and business development of MSMEs. Additionally, NLP-based marketing, which leverages persuasive communication and emotional engagement techniques, positively influences consumer relationships, loyalty, and business growth. The integration of digital marketing and NLP marketing strategies produces a synergistic impact that surpasses the individual effects of each approach. The study is limited to MSMEs in East Java and may not fully reflect conditions in other regions. Future research could expand the geographical scope or explore sector-specific dynamics for deeper insights. The results provide practical insights for MSME actors and policymakers on the importance of combining technological tools with psychological marketing approaches to enhance competitiveness and sustainability. This study contributes to the existing body of knowledge by combining digital marketing with NLP-based strategies, highlighting their joint impact on MSME welfare and growth—an area rarely explored in the Indonesian context.